Rhodamine-Sulphuric Acid -A New Visualization Reagent for the Determination of Sucralose by HPTLC - Mohd Idris; Seema Srivastava; T. R. Baggi; S. K. Shulka; A. K. Ganjoo (E-Journal of Chemistry)
Sucralose a UV-visible inactive compound was separated on silica gel plate without any plate treatment prior to analysis, derivatized with rhodamine - sulphuric acid reagent and detected densitometrically at 456 nm as olive green band. With this reagent sucralose also shows golden yellow fluorescence at 366 nm. Two new solvent systems i.e. chloroform: methanol: toluene (v/v 5:3.5:1.5) (solvent system-I) and chloroform: ethanol: benzene (v/v 5:3:2) (solvent system-II) were developed and giving Rf values of 0.62 and 0.45 respectively. The method was found to be sensitive with good limit of detection (LOD) for two solvent systems. The method imparts specificity to the method as at 456 nm sucralose only gives olive green color spots where as other artificial sweeteners did not show any response to this reagent, where as carbohydrates gives black color spots. Similarly sucralose gives golden yellow fluorescence at 366 nm which is not given by any other artificial sweetener. The method was highly reproducible with relative standard deviation (RSD)≤3% (n=3) and was applied for the determination of sucralose in different matrices like cola drinks, lemon juices, sugar free sweets, tabletop sweeteners etc.etc.